Study of the effect of pain on postoperative rehabilitation of patients with uterine malignant tumor - Lv, Xiaohong; Li, Chunlai; Tang, Min; Yuan, Dan; Zhong, Yu; Xie, Yubo (Frontiers in Surgery, 2023)
Abstract Objective: The relationship between acute postoperative pain (APSP) and health-related quality of life (HRQoL) in patients with uterine malignant tumor after operation was evaluated with self-rating scales, and the influencing factors of postoperative rehabilitation were screened. Methods: A total of 102 patients undergoing elective surgery for Gynecology in the First Affiliated Hospital of Guangxi Medical University were included in this study. PCS, SAS, NRS and EQ-5D scales were evaluated 1 day before surgery, and NRS and EQ-5D scales were evaluated 1,3,7,14, and 30 days after surgery. In addition, the general and perioperative information of patients was collected from the medical record system of the hospital. Results: From the 1st to the 30th day after operation, the NRS and EQ-5D-5L scores of patients decreased gradually, and EQ-VAS scores increased gradually. NRS score was correlated with EQ-5D score (P<0.01). Postoperative hospital stay, Education level, PCS score and NRS score (Overall state and Active state) were the principal influencing factors of EQ-5D score (P<0.05). Patients in the pain group had a later time to get out of bed and eat, a higher incidence of postoperative complications, and a longer postoperative hospital stay (P<0.05). Endoscopic surgery can reduce postoperative pain and promote postoperative rehabilitation (χ2=37.631, P<0.001). Conclusions: The postoperative rehabilitation of patients in the pain group was poor. Minimally invasive surgery can reduce postoperative pain and promote postoperative rehabilitation. EQ-5D score can be used as a subjective index to evaluate postoperative rehabilitation.